A strain-engineered self-intercalation Ta9Se12 based bifunctional single atom catalyst for oxygen evolution and reduction reactions - Huang, Hai-Cai; Wang, Ting-Ting; Li, Jun; Chen, Jing; Bu, Yuxiang; Cheng, Shi-Bo (Applied surface science, 2022)
A self-intercalation Ta9Se12 supported Pd SAC was evidenced to be a promising bifunctional catalyst for OER and ORR under strain. [Display omitted] •The Ta intercalation can effectively improve the stability and activity of supported SACs.•Some intercalated SACs with high performance were identified for OER and ORR, respectively.•Pd-Ta9Se12 was evidenced to be a promising bifunctional catalyst under a 3 % tensile strain.•Charge transfer to the surface is the origin for the enhancement of stability and activity of SAC. Seeking and designing stable, high-efficiency, and economical bifunctional catalysts for the metal-air battery is challenging but of great significance towards the conversion and storage of renewable energy. In this study, based on first principles calculations, the oxygen evolution (OER) and oxygen reduction reaction (ORR) catalytic performance of different transition-metal (TM) atoms embedded into the surface of the self-intercalation structure Ta9Se12 (TM-Ta9Se12) were evaluated. The results demonstrate that the self-intercalated Ta-layer obviously improves the stability and catalytic activity of the system. Remarkably, Pd-Ta9Se12 under a tensile strain of 3 % was identified as an efficient bifunctional catalyst for OER and ORR with overpotentials of 0.65 and 0.42 V, respectively. Mechanistically, the intercalation structure of Ta9Se12 leads to a charge accumulation in the inner layer. But divertingly, under an external force, the charge in the inner layer will diffuse to the surface. This curious phenomenon can provide the possibility for directional and continuous regulation of the catalytic performance of the catalysts. This work elucidates a new approach for designing high-efficient and stable bifunctional SACs for OER and ORR.